Journeys through the Russian Empire : the photographic legacy of Sergey Prokudin-Gorsky - Brumfield, William Craft, 1944- (Duke University Press, 2020)
"JOURNEYS THROUGH THE RUSSIAN EMPIRE will contain about four hundred photographs, accompanied by historical contextualization. The project compares William Brumfield's photographs of churches and locations in Russia with the same structures and places photographed by Sergei Prokudin-Gorsky, an early-20th-century Russian inventor of a color photography process, as much as a century earlier. Through this comparison, Brumfield assesses the state of preservation of Russia's architectural heritage and examines the appeal and pitfalls of seeing Prokudin-Gorsky's striking images as a recovery of Russia's lost past. Brumfield examines fervent Russian engagement with the Prokudin-Gorsky collection, which was recently made broadly available through digitization. The author questions the nostalgic assumptions of many analysts, who see the images as a portrayal of an idyllic Russia intact before the Soviet era and neglect the imperial violence present before the revolution. Prokudin-Gorsky himself was idealistic about the imperial potential. He intended his new color photography to convey the cultural and ethnic diversity of the vast Russian Empire, using this medium to impart a visual message from the provinces to the urban centers about the richness of Russia's history, culture, and borderlands. He escaped Russia in 1918 with many of the heavy glass negatives he used, and the Library of Congress ultimately bought the collection. Because of his own field experience photographing Russian architectural monuments, Brumfield was approached to catalog, restore, and exhibit Prokudin-Gorsky's photographs. While working on the project, he realized how much the two photographer's journeys across Russia had, unintentionally, intersected. His own photographic project accelerated with the relaxation of travel restrictions within the Soviet Union during the late 1980s; he documents the remnants of Russia's architectural heritage, and its expression of history, art, and spiritual culture, that Prokudin-Gorsky recorded earlier. This project will be of particular interest to scholars and students of Russian history, art, and architecture, as well as general readers interested in photography and historic preservation"--